Microstructural analysis of siderurgical aggregate concrete reinforced with fibers. (1st April 2023) - Aghajanian, A.; Cimentada, A.; Behfarnia, K.; Brand, A.S.; Thomas, C.
Abstract: The development of cracks in concrete structures is one of the significant issues with maintaining high strength after hardening. One way to prevent and control this problem is to use fibers. This paper investigates concrete containing electric arc furnace slag aggregates reinforced with fibers. The fibers used in this study are steel fibers and three kinds of polypropylene fibers; polyolefin fibers (modified polypropylene), polypropylene homopolymer, and high-toughness polypropylene. By checking the compressive and flexural strength of concretes made with fibers, it can be seen that the best results at 28 days are found for concrete with steel fibers, namely 62 MPa with 0.9% of fibers. On the contrary, the lowest values are for concrete containing polyolefin fibers, 51 MPa, and the same percentage of fibers. Additionally, under flexural strength testing, at the age of 28 days, the strength of these samples with 0.9% of fibers was 9.54 MPa, a value that is comparable to test concrete with the same percentage of steel fibers, 10.67 MPa, despite the low workability of concrete containing polyolefin fibers with a slump of 25 mm. Moreover, the boundary transition area analysis shows that the excellent connection between the fibers and cement paste near the siderurgical aggregate has caused no cracks in this area. In contrast, cracks can be observed in critical areas near the natural aggregates. Highlights: Compared to other fibers, polyolefin fibers cause the most slump loss. No polypropylene fibers can compete with steel fibers in terms of compressive strength. Steel and polyolefin fibers have a close behavior in flexural strength. Polypropylene fibers have a good bonding with cement paste in the interfacial transition zone.